Adaptation to risks related to ecotourism: development at Boabeng in the Bono East Region, Ghana - Thomas Yeboah; Charles Senior Afram; Bernice Quampah; Ahmed Kulega (Goodwood Publishing, 2019)
Purpose: The purpose of this study was to evaluate adaptation strategies developed by residents in order to minimize the risks caused by the ecotourism project at Boabeng in the Bono East region of Ghana. Research methodology: Data collection instruments included schedules and interview guides. A sample of 404 heads of households was randomly selected for the administration of schedules, whilst 12 respondents each were purposively selected for focus group discussions and indepth interviews. Household data were analyzed using percentages, frequencies and mean responses. Findings: Findings indicate that households adapted to ecotourism risks by patrolling and farming off the feeding range of the monkeys. Limitations: Household heads and opinion leaders were made to assess the ecotourism project in terms of how they cope with it. These community leaders, some of whom were direct beneficiaries of the projects, may not give the right information and this may affect the results of the study. Respondents were however; assured of confidentiality of their responses so as to enable them give the right information on their adaptation to risks related to the ecotourism project in the community. Contribution: This study recommends the intensification of livelihood diversification schemes in the study area. Keywords: Destination, Limitations, Livelihood diversification, Local community, Local households, Monkey sanctuary, Vulnerable households